1988
DOI: 10.1159/000118483
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin (DDAVP) Therapy in Chronic Schizophrenia: Effects on Negative Symptoms and Memory

Abstract: Ten chronic undifferentiated schizophrenics, 6 men and 4 women, aged 28–63, with 6- to 31-year histories of the disease were given DDAVP to observe the effects of this neuropeptide on the prevalent negative symptoms of their illness. Patients were maintained on neuroleptic therapy and first given a 20-day course of placebo followed by 20 days of DDAVP i.m., 4 µg. Andreasen Scale for assessment of negative symptoms, the Brief Psychiatric Rating Scale, the NOSIE Rating Scale and the Luria-Nebraska Rating Scale w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
(33 reference statements)
3
16
1
Order By: Relevance
“…Semantic recognition was not im proved and there was no effect on nonspecific arousal as assessed by visual reaction time [Millar et al, 1987], In schizophrenic patients. DDAVP improved short to me dium memory with no parallel increase in attention [Brambilla et al, 1988], The significant improvement of memory by DGAVP in the present study without effects on vigilance is con tradictory to a recent observation on arginine vasopres sin, which increased vigilance without effects on mem ory in student volunteers [Fehm-Wolfdorf et al, 1988]. Thus, the analogue DGAVP may have a profile of action that differs from the physiological substance in man.…”
Section: Discussionsupporting
confidence: 83%
“…Semantic recognition was not im proved and there was no effect on nonspecific arousal as assessed by visual reaction time [Millar et al, 1987], In schizophrenic patients. DDAVP improved short to me dium memory with no parallel increase in attention [Brambilla et al, 1988], The significant improvement of memory by DGAVP in the present study without effects on vigilance is con tradictory to a recent observation on arginine vasopres sin, which increased vigilance without effects on mem ory in student volunteers [Fehm-Wolfdorf et al, 1988]. Thus, the analogue DGAVP may have a profile of action that differs from the physiological substance in man.…”
Section: Discussionsupporting
confidence: 83%
“…A post-mortem study of tissue AVP concentrations found decreased AVP amounts in the temporal lobe of schizophrenic brain tissue, but the hypothalamic content was not different from controls (Frederiksen et al, 1991). AVP analogues have been shown to be effective adjunctive treatments of schizophrenic symptoms, particularly negative spectrum symptoms (Brambilla et al, 1986(Brambilla et al, , 1989Iager et al, 1986), and poorly controlled trials reporting psychotic symptom improvement after OT administration also exist (Bujanow, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…DDAVP, a synthetic VP agonist, produced improvements in negative symptom profiles in schizophrenia patients [24,[27][28][29][30]. However, DDAVP did not improve cognitive performance in humans with amnesia [31].…”
Section: Crossmarkmentioning
confidence: 98%
“…VP is also involved in behavioral outcomes important in the etiology of schizophrenia such as learning and memory, aggression, and sociality [23]. In addition, both glutamate and VP antagonism have been associated with negative symptoms of schizophrenia, suggesting a potential interaction between glutamate and VP signaling in the brain [24][25][26]. Moreover, there is evidence that VP activity in the hypothalamus may be regulated by glutamatergic signaling [22].…”
Section: Crossmarkmentioning
confidence: 99%
See 1 more Smart Citation